Maternal health around pregnancy and autism risk: a diagnosis-wide, population-based study. Issue 16 (26th December 2022) - Kodesh, Arad; Levine, Stephen Z.; Khachadourian, Vahe; Rahman, Rayees; Schlessinger, Avner; O'Reilly, Paul F.; Grove, Jakob; Schendel, Diana; Buxbaum, Joseph D.; Croen, Lisa; Reichenberg, Abraham; Sandin, Sven; et al.
Abstract: Background: Many studies have reported an increased risk of autism spectrum disorder (ASD) associated with some maternal diagnoses in pregnancy. However, such associations have not been studied systematically, accounting for comorbidity between maternal disorders. Therefore our aim was to comprehensively test the associations between maternal diagnoses around pregnancy and ASD risk in offspring. Methods: This exploratory case–cohort study included children born in Israel from 1997 to 2008, and followed up until 2015. We used information on all ICD-9 codes received by their mothers during pregnancy and the preceding year. ASD risk associated with each of those conditions was calculated using Cox proportional hazards regression, adjusted for the confounders (birth year, maternal age, socioeconomic status and number of ICD-9 diagnoses during the exposure period). Results: The analytic sample consisted of 80 187 individuals (1132 cases, 79 055 controls), with 822 unique ICD-9 codes recorded in their mothers. After extensive quality control, 22 maternal diagnoses were nominally significantly associated with offspring ASD, with 16 of those surviving subsequent filtering steps (permutation testing, multiple testing correction, multiple regression). Among those, we recorded an increased risk of ASD associated with metabolic [e.g. hypertension; HR = 2.74 (1.92–3.90), p = 2.43 × 10 −8 ], genitourinary [e.g. non-inflammatory disorders of cervix; HR = 1.88 (1.38–2.57), p = 7.06 × 10 −5 ] and psychiatric [depressive disorder; HR = 2.11 (1.32–3.35), p = 1.70 × 10 −3 ] diagnoses. Meanwhile, mothers of children with ASD were less likely to attend prenatal care appointment [HR = 0.62 (0.54–0.71), p = 1.80 × 10 −11 ]. Conclusions: Sixteen maternal diagnoses were associated with ASD in the offspring, after rigorous filtering of potential false-positive associations. Replication in other cohorts and further research to understand the mechanisms underlying the observed associations with ASD are warranted.